Medidas de gestión para la sostenibilidad ambiental de la jaiba azul Callinectes sapidus a partir de información biológica y socioeconómica de la comunidad pesquera en la zona nor-oriental de la Ciénaga Grande De Santa Marta (CGSM), caribe colombiano (2022)
To determine the biological, economic, and environmental aspects that influence the blue crab fishery (Callinectes sapidus) in the Ciénaga Grande de Santamarta (CGSM), in order to propose management measures for the sustainability of the species. 2346 catches were made in the northeastern part of the CGSM and 25 fishermen were surveyed in sectors of the Rosario and Tasajera districts of the municipality of Pueblo Viejo. From the specimens collected from blue crab in 2018 (July to December) and 2021 (August), biometrics were carried out in which the size structure, weight and sexual maturity were analyzed, to estimate the degree of utilization; This indicated a moderate operating risk, with 47% of the catches below the average maturity size (BMR) established in resolution 623 of 2004. Between the months of September and December (2018) there were increases in catches with a ratio of 9:2 (females: males); while in the month of August the largest Abel (9,55 cm), Lca (5,74 cm) and weight (106 gr) were recorded. In determining the socioeconomic aspects using the surveys, it was found that 44% of the fishermen used to catch crab the nasa and the relera and the propulsion method is the oar (36%), in addition they share the area even with more than thirteen boats; In addition, the operating costs were analyzed, the most relevant being the feeding, the bait, the repairs of the canoe and the daily economic income ($34111 COP/kg). According to the information collected, fishing management measures were suggested, such as selective fishing gears, environmental awareness, improvement of control systems, updating of minimum sizes, among others. To integrate people considering the current situation and perspectives, to promote the environmental sustainability of blue crab in the CGSM and to serve as a basis and support in fisheries management processes.